THE ROLE OF MARKETING MIX STRATEGIES IN CONSUMER CONVENIENCE OF RURAL BANKS IN NORTH SUMATERA - Nikous Soter Sihombing; Sunday Ade Sitorus; SUNDAY ADE SITORUS (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Rural Banks has the opportunity to increase third party fund in the form of saving and pension credit distribution. Both purposes can be achieved by increasing pensioner customers who make Rural Banks the paymaster of their pension fund. If this problem did not meet the solution or the right handling, it might increase the stagnant customers so that Rural Banks would lose the opportunity to increase third party fund and profit from loan distributed. The purpose of this study was to find out the marketing mix factor that most influence to the customer convenience at the Rural Banks . This is intended to help formulate a marketing strategy to attract customer to become product customer and increase Rural Banks, saving and credit volume. In this study, the method used was survey approach. The type of this study was quantitative descriptive and the nature of this study was descriptive explanatory. Data collection method was carried out using questionnaire and documentation. The data analysis used was multiple regression. Simultaneously, the result showed that the price variable had no effect on the customer convenience to become a customer at the Rural Banks, but the location variable had a strong influence on the decision to become a product customer at the Rural Banks. Product, location, promotion, price, person, and process variables simultaneously had a positive and significant effect on the increase the number of retirees at Rural Banks. This showed that with product offered according to need, location that was easy to reach, attractive promotion, employees who were friendly and working well, a fast process and affordable credit interest rates could boost the positive impact on increasing the number of customers at the Rural Banks, .